Electroporation-Mediated Gene Delivery - Young, Jennifer L. (Adv Genet, 2014)
Electroporation has been used extensively to transfer DNA to bacteria, yeast, and mammalian cells in culture for the past 30 years. Over this time, numerous advances have been made, from using fields to facilitate cell fusion, delivery of chemotherapeutic drugs to cells and tissues, and most importantly, gene and drug delivery in living tissues from rodents to man. Electroporation uses electrical fields to transiently destabilize the membrane allowing the entry of normally impermeable macromolecules into the cytoplasm. Surprisingly, at the appropriate field strengths, the application of these fields to tissues results in little, if any, damage or trauma. Indeed, electroporation has even been used successfully in human trials for gene delivery for the treatment of tumors and for vaccine development. Electroporation can lead to between 100 and 1000-fold increases in gene delivery and expression and can also increase both the distribution of cells taking up and expressing the DNA as well as the absolute amount of gene product per cell (likely due to increased delivery of plasmids into each cell). Effective electroporation depends on electric field parameters, electrode design, the tissues and cells being targeted, and the plasmids that are being transferred themselves. Most importantly, there is no single combination of these variables that leads to greatest efficacy in every situation; optimization is required in every new setting. Electroporation-mediated in vivo gene delivery has proven highly effective in vaccine production, transgene expression, enzyme replacement, and control of a variety of cancers. Almost any tissue can be targeted with electroporation, including muscle, skin, heart, liver, lung, and vasculature. This chapter will provide an overview of the theory of electroporation for the delivery of DNA both in individual cells and in tissues and its application for in vivo gene delivery in a number of animal models.